Public mental health and the COVID-19 pandemic - Ashton, John R. (Ir J Psychol Med, 2021)
COVID-19 has presented society with a public health threat greater than any in living memory, leaving us to question almost every aspect of our society. An ever increasing concern is how we protect the global population from mental illness and whether public mental health policies can achieve this. In this article I reflect on the history of mental health service development, and furthermore on how COVID-19 might impact on the delivery of public mental health strategies into the future.